Investigating the importance of self-theories of intelligence and musicality for students' academic and musical achievement - Müllensiefen, Daniel; Harrison, Peter; Caprini, Francesco; Fancourt, Amy (Frontiers in Psychology, 2015)
Musical abilities and active engagement with music have been shown to be positively associated with many cognitive abilities as well as social skills and academic performance in secondary school students. While there is evidence from intervention studies that musical training can be a cause of these positive relationships, recent findings in the literature have suggested that other factors, such as genetics, family background or personality traits, might also be contributing factors. In addition, there is mounting evidence that self-concepts and beliefs can affect academic performance independently of intellectual ability. Students who believe that intelligence is malleable are more likely to attribute poor academic performances to effort rather than ability, and are more likely to take remedial action to improve their performance. However, it is currently not known whether student's beliefs about the nature of musical talent also influence the development of musical abilities in a similar fashion. Therefore, this study introduces a short self-report measure termed “Musical Self-Theories and Goals,” closely modeled on validated measures for self-theories in academic scenarios. Using this measure the study investigates whether musical self-theories are related to students' musical development as indexed by their concurrent musical activities and their performance on a battery of listening tests. We use data from a cross-sectional sample of 313 secondary school students to construct a network model describing the relationships between self-theories and academic as well as musical outcome measures, while also assessing potential effects of intelligence and the Big Five personality dimensions. Results from the network model indicate that self-theories of intelligence and musicality are closely related. In addition, both kinds of self-theories are connected to the students' academic achievement through the personality dimension conscientiousness and academic effort. Finally, applying the do-calculus method to the network model we estimate that the size of the assumed causal effects between musical self-theories and academic achievement lie between 0.07 and 0.15 standard deviations.